Electrochemical Energy Storage: Harnessing the Extracellular Electron Transfer Capability of Geobacter sulfurreducens for Ambient Synthesis of Stable Bifunctional Single‐Atom Electrocatalyst for Water Splitting (Adv. Funct. Mater. 22/2021). (26th May 2021) - Pedireddy, Srikanth; Jimenez‐Sandoval, Rodrigo; Ravva, Mahesh Kumar; Nayak, Chandrani; Anjum, Dalaver H.; Jha, Shambhu Nath; Katuri, Krishna P.; Saikaly, Pascal E.
Abstract : In article number 2010916, Srikanth Pedireddy, Pascal E. Saikaly, and co‐workers report a facile synthesis strategy of single‐atom catalysts (SACs) at room temperature by harnessing the extracellular electron transfer capability of Geobacter sulfurreducens . This strategy can be successfully extended for the synthesis of various transition metal SACs by merely altering the metal precursors. Without further heat treatment, the dried catalysts exhibit excellent electrocatalytic activity for oxygen and hydrogen evolution reactions.